(untitled) (Revista Venezolana de Salud Pública, 2016)
n 1578, twenty-five years after the city of Nueva Segovia de Barquisimeto was founded, the first sick care center was created in Lara State and Venezuela, which were attended by slaves, this sick shelter was called "Hospital de Santiago" organized by the Spanish conquerors and promoted by the Cleric Pedro del Castillo, it would later be called "Hospital of San Lazaro" that would prevail between 1812 and 1837. Then the "Hospital de La Caridad" was inaugurated in 1918 (Figures 1, 2 and 3) by its main promoter, Dr. Antonio María Pineda, built on the "solar or patio" where the former San Lázaro Hospital (1,2,3), on Obispo Street, (currently Carrera 15 between streets) 25 and 26 of Barquisimeto, Lara State, Venezuela), operating there until 1954, when it would move to its current headquarters north of Avenida Vargas de Barquisimeto, being for this moment the best hospital structure of Venezuela (Figure 4). The Director of the Hospital La Caridad, brought the sisters of La Caridad (Sisters of St. Joseph of Tarbes), who promoted the charity bazaars, organized by the Daughters of Charity Society, which Dr. Pineda himself trained in Barquisimeto, Cabudare , Quibor, Siquisique, Bobare, Yaritagua and Río Claro (Lara and Yaracuy states), where Las Daughters of La Caridad, not only collected money, but all kinds of objects that were raffled, highlighting especially an activity for the benefit of the Hospital carried out in the old Teatro Juárez (Barquisimeto, Venezuela), on April 19, 1918 (declared charity day) (1,2,3).